Recovery from different high-intensity interval training protocols: comparing well-trained women and men - Hottenrott, L.; Möhle, M.; Ide, A.; Ketelhut, S.; Stoll, O.; Hottenrott, K. (Sports, 2021)
Due to physiological and anatomical sex differences, there are variations in the training response, and the recovery periods following exercise may be different. High-intensity interval training (HIIT) protocols are well-suited to differentially investigate the course of recovery. This study was conducted to determine sex-specific differences in the recovery following HIIT intervals interspersed with recovery phases of different lengths. Methods: Well-trained cyclists and triathletes (n = 11 females, n = 11 males) participated in this study. There were no significant sex differences in maximal heart rate (HR), relative peak power to body mass and fat-free mass, training volume, and VO2max-percentiles (females: 91.8 ± 5.5 %, males: 94.6 ± 5.4 %). A 30 s Wingate test was performed four times, separated by different active recovery periods (1, 3, or 10 min). Lactate, HR, oxygen uptake, and subjective rating of exertion and recovery were determined. Results: For the recovery time of three and ten minutes, men showed significantly higher lactate concentrations (p = 0.04, p = 0.004). Contrary, HR recovery and subjective recovery were significant slower in women than in men. Conclusion: During HIIT, women may be more resistant to fatigue and have a greater ability to recover metabolically, but have a slower HR and subjective recovery